Analysis of Tiktok Use on Sales at Cafe Lazeez Medan Tembung - Meiriza, Mica Siar; Sigalingging, Renaldi Enriko; Sitorus, Monika Caramoy; Ginting, Flowrensari Haggata; Sanjaya, Adika (CV. Rayyan Dwi Bharata, 2025)
Tiktok has become one of the most influential social media platforms in digital marketing strategies, especially for businesses in the culinary industry. This study aims to analyze the impact of Tiktok usage on sales at Lazeez cafe using a qualitative approach. The research method employed is a case study, with data collection techniques including in-depth interviews with the cafe owner, employees, and customers, as well as observations of marketing activities and interactions on Tiktok. The findings indicate that effective use of Tiktok, through creative content and active user engagement, contributes to increased customer interest and cafe visits. Factors such as content virality, customer testimonials, and branding strategies through Tiktok play a crucial role in enhancing the cafe’s appeal. Thus, this study confirms that Tiktok can serve as an effective marketing tool for building brand awareness and boosting sales in the culinary sector, particularly for businesses like Lazeez cafe.